Sustainability of the youth agriculture empowerment programmes in Osun and Oyo states (2018)
The problem of youth unemployment in Nigeria necessitated both the federal and state governments to introduce several empowerment programmes particularly in agriculture in order to enhance the economic capacity of youths. However, some of these programmes barely outlive the political regime that initiated them. Meanwhile, Osun youth empowerment programme has been acclaimed to be a model copied by other local and international organisations. Therefore, this study investigated sustainability of youth empowerment programmes in agriculture in Osun and Oyo States. Three (3) Local Government Areas (LGA) with 25% of the beneficiaries were selected randomly from each of the two states to give a total of 260 respondents. Data were collected using structured questionnaire and analysed using descriptive and inferential statistics at α0.05. The study revealed more male participation in the programme in both states, high formal education with mean age of 28.2 (Osun) and 31.5 years (Oyo). Major benefit derived by respondents was positive attitudinal change towards agriculture (Osun=96.1%, Oyo= 73.5%) and job opportunity (Osun=91.6%, Oyo=87.4%) Respondents’ level of participation in the programme was low (Osun=56.1%, Oyo= 58.4%), 60.6% and 89.3% in Osun and Oyo respectively perceived the programme to be unsustainable. Inadequate funding, lack of post empowerment support and monitoring were the major constraints to sustainability There was a significant relationship between benefits derived (r = 0.398) by respondents’ in Oyo, constraints in both states (Osun =0.243, Oyo = 0.855) and sustainability of the programme. The youth empowerment programme in agriculture in both states was adjudged unsustainable. Monitoring and evaluation process as well as, appropriate legislation to insulate the programme from political shocks should be included from onset.